Prospective Randomized Controlled Study of Hemostatic Efficacy with Kaolin-Impregnated Dressings in Diabetic Foot Ulcers Taking Anticoagulants Undergoing Debridement in an Outpatient Clinic - Yeok Gu Hwang; Jin Woo Lee; Eun Ae Won; Seung Hwan Han (Journal of Diabetes Research)
Background. The effective hemostasis after minor debridement in an outpatient clinic is important and essential. This study is aimed at evaluating the hemostatic efficacy and safety of the kaolin-impregnated dressing for diabetic foot ulcer patient who take an anticoagulant. Methods. A prospective, randomized, clinical trial study was performed in twenty-six patients with diabetic foot ulcers who take an anticoagulant requiring minor debridement in an outpatient clinic. Minor debridement and removal of break down skin were performed by one orthopedic surgeon. Hemostasis on wound bed was achieved using kaolin-impregnated gauze (study group) and standard sterilized dry gauze (control group). Two randomized groups were compared for hemostatic efficacy and side effect. Results. For the purpose of this study, the presence or absence of hemostasis was assessed at 5 and 10 minutes after the application of dressing material. Treatment was evaluated as successful if bleeding was ceased adequately, and no extra hemostatic measures were required within 10 minutes. At 5 minutes, 80% of patients using the kaolin-impregnated gauze successfully achieved complete hemostasis versus 40% in the control group that controlled bleeding partially. With kaolin-impregnated gauze, 100% of patients show complete hemostasis at 10 minutes versus 58.3% in the standard gauze (P<.001). An adverse effect was not noted in all patients. Conclusions. The use of kaolin-impregnated gauze appears to be a safe and feasible option in managing bleeding after debridement of diabetic foot ulcers, and merits to patient who had a bleeding tendency is high. This trial is registered with CRIS registration number KCT0003894.